PENDAMPINGAN PEMANFAATAN MEDIA INSTAGRAM SEBAGAI MEDIA DAKWAH PRM KARANGREJO - Maulana Arif Muhibbin; Muhammad Zainur Ridlo; Putra Kurniawan (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
The community service activity was held at the Muhammadiyah Branch Leadership of Karangrejo with the aim of providing an understanding to the Muhammadiyah administrators in Karangrejo Village about the use of technology as a medium for delivering Islamic da'wah in the Industry 4.0 era. The digital platform taught was the Instagram social media because it has complete features and is widely used by young people today. This program was carried out with a participatory approach through several stages of implementation, namely: 1) an initial meeting to agree on a collaboration for the community service activity with partners, 2) mapping the needs for digital da'wah, 3) creating digital content, and 4) providing guidance. This activity successfully enhanced the administrators' skills in digital da'wah and resulted in accounts and da'wah content using the Instagram platform. With the digitization of da'wah, it is hoped that PRM Karangrejo can contribute to modern and progressive Islamic propagation